PENGARUH SUHU DAN OKSIGEN TERLARUT TERHADAP TINGKAT METABOLISME DAN KELANGSUNGAN HIDUP LARVA IKAN BAUNG Mystus nemurus Cuv & Val - Usman Muhammad Tang; Ridwan Affandi; R. Widjajakusuma; Heru Setijanto; M. F. Rahardjo (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2000)
The rearing technology of green catfish larvae has not yet established. Hight mortality occurred in the early larval stages. This experiment was conducted to study the effect of temperature and dissolved oxygen on metabolic rate and survival rate of green catfish larvae. 3600 green catfish larvae with initial individual mean weights of 1.24 ±0.19 mg and lengths 5.85 ±0.71 mm (one day after hatching) were reared in the aquarium of 30 cm x 30 cm x 40 cm dimension. Treatments were done at 3 levels of temperature 27oC, 30oC, and 33oC; and 3 levels of dissolved oxygen 6.47 ml/L, 1.05 ml/L, and 0.78 ml/L and 3 replications. The result showed that temperature and dissolved oxygen was significant to the oxygen consumption. Oxygen consumption of 0.67 ±0.25 mg O2/h/g and 0.86 ±0.005 mg O2/h/g was highest in larval reared at 33oC and dissolved oxygen 6.47 ml/L for 3 weeks. The higher water temperature the greater the oxygen consumption. The oxygen consumption decline with decreasing dissolved oxygen in the water, indicating an axyconformer type. The temperature was not significant to the survival rate and growth of the larvae. However the effect of dissolved oxygen was significant to the growth rate (P<0.05). Growth rate of 25.69 ±0.55% was highest in larval reared at 6.47 mg/L for 3 weeks.